PENGARUH STRATEGI DEVELOPMENTALLY APPROPRIATE PRACTICE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS Dl SMP NEGERI 1 TANJUNG BATU - Rosalina Rosalina; Yulia Djahir; Fitriyanti Fitriyanti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
Problem formulation in this research is Is there any difference of influence of strategy of developmentally appropriate practice with strategy to enliven learning atmosphere to student learning result in IPS subject in SMP Negeri 1 Tanjung Batu ?. This research design uses true experimental design with pretest posttest control group design. The population in this study is all students of class VIII consisting of 4 classes with a total of 127 students. By using Cluster Random Sampling technique, there are two classes, namely class VIII I as the experimental class which amounted to 32 people and class VIII 2 as the control class which amounted to 32 people. Data collection techniques were obtained using tests and observations. Data analysis technique used is prerequisite test and hypothesis test with t-test formula. Based on the analysis of test data on t-test obtained t arithmetic or 2, 765> 1, 999 then Ho rejected and Ha accepted. Thus the hypothesis proposed in this study is acceptable truth, that there are differences in the influence of strategy developmentally appropriate practice with the strategy of enabling the learning atmosphere of student learning outcomes in the subjects of social studies in SMP Negeri 1 Tanjung Batu. Based on the results of observational data analysis in the experimental class that is 93.3% and 88.9% control class so that can be interpreted the learning activities conducted by researchers very well. So it is suggested to the teacher to apply the strategy of developmentally appropriate practice in the learning process